Gambia : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
In the Gambia, effective public financial management is promoted through a reasonably sound budget framework. However, there are a number of serious weaknesses, which create a high level of fiduciary risk. (Appendix 1 of this report.) Fiduciary risk means here that there is a risk that resources are not accounted for properly, that they are not used for intended purposes and that expenditure does not represent value for money. There are also risks associated with the governance environment. These weaknesses include poor resource allocation, non-compliance, limited execution, inadequate monitoring and scrutiny, insufficient capacity, lack of enforcement, non-transparency, and poor parliamentary oversight. The Government's pledge to strengthen governance needs to be translated into measures to address these weaknesses. This report recommends the following recommendations for providing evidence that significant progress has been made towards the fundamental benchmarks in public financial management: 1) Strengthen linkages between policies and budget expenditures through updating sectoral public expenditure reviews (PERs) for education, health, and agriculture & natural resources, and completing two new PERs in the infrastructure (transportation) and local government sectors. 2) Provide spending departments with indicative resource envelopes beyond the coming month/quarter to facilitate their planning and management. 3) Update the accounting records (including bank reconciliations), immediate address concerns with information technology systems (OMICRON, WANG) and urgently close the annual accounts. 4) Issue audit opinions on financial statements for 1991-1999.